2020
DOI: 10.1097/cce.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Camostat Mesylate May Reduce Severity of Coronavirus Disease 2019 Sepsis: A First Observation

Abstract: Objectives: Severe acute respiratory syndrome coronavirus 2 cell entry depends on angiotensin-converting enzyme 2 and transmembrane serine protease 2 and is blocked in cell culture by camostat mesylate, a clinically proven protease inhibitor. Whether camostat mesylate is able to lower disease burden in coronavirus disease 2019 sepsis is currently unknown. Design: Retrospective observational case series. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 13 publications
3
39
1
Order By: Relevance
“…These clinical trials are running in Denmark (CamoCO‐19, NCT04321096), USA (RECOVER, NCT04470544, NCT04353284, NCT04524663, NCT04374019), UK (NCT04455815), Mexico (NCT04530617), Israel (COSTA, NCT04355052), Germany (NCT04338906), South Korea (NCT04521296) and Japan (NCT04451083) and should provide valuable insight into the potential utility of camostat mesylate in treating COVID‐19. A recent open‐label case‐control study with camostat mesylate on COVID‐19 intensive care patients shows promise for these ongoing trials 58 …”
Section: Discussionmentioning
confidence: 99%
“…These clinical trials are running in Denmark (CamoCO‐19, NCT04321096), USA (RECOVER, NCT04470544, NCT04353284, NCT04524663, NCT04374019), UK (NCT04455815), Mexico (NCT04530617), Israel (COSTA, NCT04355052), Germany (NCT04338906), South Korea (NCT04521296) and Japan (NCT04451083) and should provide valuable insight into the potential utility of camostat mesylate in treating COVID‐19. A recent open‐label case‐control study with camostat mesylate on COVID‐19 intensive care patients shows promise for these ongoing trials 58 …”
Section: Discussionmentioning
confidence: 99%
“…An alternative and probably safer, versus ACE2 inhibition, approach would be the use of TMPRSS2 inhibitors. TMPRSS2 is druggable and camostat mesylate partially blocked SARS-CoV-2 cell infection [ 4 ] while preliminary reports showed that it reduced the severity of COVID-19 sepsis [ 86 ]; thus, several clinical trials are currently ongoing to test whether camostat mesylate could be repurposed and utilized to combat the current pandemic [ 87 ]. TMPRSS2 inhibition could also reduce viral tropism at the initial site of SARS-CoV-2 infection and enhance anti-viral humoral immune responses of the host [ 88 , 89 ].…”
Section: Targeting the Life Cycle Of The Virusmentioning
confidence: 99%
“… Akin to Kumar and colleagues, the essential role of transmembrane protease serine 2 (TMPRSS2) co-expression in mediating the SARS-CoV-2 cellular entry, has captivated the attention of the fraternity [3] , [4] , [5] , [6] . In this context, the TMPRSS2 inhibitors such as camostat mesylate (CM) and nafamostat mesylate (NM) are being currently envisaged as promising repurposed drugs (approved for treating pancreatitis in Japan) in COVID-19 for their anti-inflammatory and antiviral properties owing to serine protease inhibition and resultant viral cellular entry block [3] , [4] , [5] , [6] . A few researchers cite an incremental value to the therapeutic inclusion of a critical host factor blocker like TMPRSS2 inhibitor over an isolated antiviral regimen, in conferring a subsequent resilience to the rapidly developing viral resistance.…”
mentioning
confidence: 99%
“…They opine that the isolated viral point mutations are unlikely to accommodate for such a critical host component block [7] . A recent retrospective observational case-series by Hofmann-Winkler et al outlined an attenuation of the COVID-19 disease severity marked by lower sepsis-related organ failure assessment (SOFA) scores paralleled by an ameliorated inflammatory profile in the six ICU patients who received CM compared to the five ICU patients treated with hydroxychloroquine [3] . The maximum CM dose administered in their evaluation amounted to 2 × 100 mg pills three times daily for 5 days which was in accordance with the protocol of a large Denmark randomized controlled trial (RCT, CamoCo-19, NCT04321096).…”
mentioning
confidence: 99%
See 1 more Smart Citation